RIGHT OF MEMBERS OF A COMPANY'S CORPORATE BODY, ITS LIQUIDATORS AND OTHER PERSONS REPRESENTING IT TO BE FORGOTTEN IN THE BUSINESS REGISTER - Skibińska, Ewa (Człowiek w cyberprzestrzeni, 2020)
The right to be forgotten is intended to safeguard the interests of individuals, including the protection of personal data in the current state of technological development and consider the needs of the information society. This paper is to analyse EU and Polish regulations concerning the right of members of corporate bodies, its liquidators and other persons representing the company to be forgotten in the business register. The publication shows that even though the GDPR has entered into force, the Court of Justice stance remains valid with regard to the Manni judgment regarding, as a matter of principle, the exclusion of these entities from the right to be forgotten. Thus, members of the governing bodies of a Polish commercial company, its liquidators and representatives cannot, in principle, rely on GDPR to exercise the right to be forgotten with respect to the data contained in the business register. Any invocation to this right arises either from national law or from the balance by the national court between, on the one hand, data protection and privacy right, on the other hand, public interest, in particular third party interest in access to data contained in the business register, coupled with the fulfilment of obligations concerning the disclosure of data on companies under EU and Polish law.